Axions Across Boundaries between Particle Physics, Astrophysics, Cosmology and forefront Detection Technologies - AAVV (Il Colle di Galileo, 2024)
The workshop brought together scientists from different backgrounds and expertise to discuss open problems, recent developments and future directions in axion physics, a field notoriously replete with interdisciplinary connections. The aim of the workshop was to foster a fruitful cross-breeding between different theoretical areas, with a focus on certain open issues in axion particle physics, astrophysics and cosmology. The interaction between the experimental and theoretical communities fostered the merging of “how to search” with “where to search” into optimised strategies to hunt for the axion.